Continuous household sampling for epidemiological research and for teaching purposes - Carvalheiro, José da Rocha; Sanches, Odécio (Revista de Saúde Pública, 1979)
The use of adequate populational-base survey is frequently impossible in epidemiological studies. Special studies are made among particular groups of individuals to investigate simultaneously the presence of both the factor and the disease. In these studies it is obviously important to use adequate sampling techniques. A system of continuous household sampling is described, designed to perform, simultaneously, epidemiological research, health system monitoring and to serve as a basis for courses on sampling techniques and epidemiological methods. In the municipality of Ribeirão Preto, S. Paulo, Brazil a household sampling system has been in operation since 1974, using a master sample of 8500 households. Every two weeks, 380 households are visited and information is gathered about diseases, accidents, and the use of health services. Special epidemiological research is introduced when necessary. Future development includes the use of standardized questionnaires and physical and laboratory examinations of the people interviewed.